Gastric cancer cell-derived exosomal miRNA-128-3p promotes angiogenesis by targeting SASH1 - Yan, Hao; Cai, Xinyu; Zhang, Jianna; Zhao, Hongpeng; Wu, Hongwen; Zhang, Jingbo; Xu, Lanzhi; Liu, Shizheng; Zang, Yuanwei; Fu, Shanshan (Frontiers in Oncology, 2024)
Exosomes, key components of the tumour microenvironment, can mediate intercellular communication through the delivery of various signalling molecules, including microribonucleic acids (miRNAs), and ultimately participate in regulating the process of tumour development. In this study, we aimed to investigate the reason and mechanism by which exosomal miRNAs derived from gastric cancer cells affect carcinogenesis and metastasis. Among these miRNAs, microRNA-128-3p (miR-128-3p) was highly expressed in serum exosomes isolated from gastric cancer patients, as confirmed by high-throughput sequencing and subsequent experiments. Coculture of gastric cancer-derived exosomes overexpressing miR-128-3p with human umbilical vein endothelial cells (HUVECs) significantly enhanced HUVEC proliferation, migratio n and angiogenesis. Bioinformatics analysis suggested SASH1 as the target gene of miR-128-3p. The dual luciferase assay and Western blot analysis results confirmed that miR-128-3p directly targeted SASH1 to inhibit its expression in HUVECs. Therefore, this study provides preliminary evidence that gastric cancer-derived exosomal miR-128-3p promotes tumour angiogenesis by targeting SASH1, reveals the potential diagnostic and therapeutic value of cancer-derived exosomal miR-128-3p, and provides new insights into the novel molecular mechanisms regulating metastasis. This study provides further information for understanding the role of gastric cancer-derived exosomal miR-128-3p in cancer progression and to discover new therapeutic targets.